The copper rush of the nineties. Issue 9 (1st August 2016) - Solioz, Marc
Abstract : The discovery of copper-transporting ATPases in the 90s led to a molecular understanding of Menkes and Wilson disease. The historic events leading up to and following these discoveries are reviewed. Abstract : The nineties witnessed the discovery of the copper ATPases, enzymes which transport copper across the cytoplasmic membranes of bacteria and eukaryotes. In the same decade, several other key components of copper homeostasis have also been discovered, like copper chaperones and plasma membrane copper transporters. This has finally led to a molecular understanding of two inherited human diseases related to copper: Menkes disease, manifested by systemic copper deficiency, and Wilson disease, caused by defective secretion of excess copper. A historic perspective and untold stories of the events leading up to these discoveries are presented here.